1995
DOI: 10.1111/j.1600-0560.1995.tb01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 7 in keratoacanthoma and squamous cell carcinoma detected by fluorescence in‐situ hybridization

Abstract: Keratoacanthoma (KA) is generally considered to be a clinically and histologically distinct entity, but it often remains difficult to separate from well-differentiated squamous cell carcinoma (WDSCC). Recently, trisomy 7 has been identified in squamous cell carcinoma of the skin. In this study, we examined classical KA (n = 6), WDSCC (n = 7) and squamous cell carcinoma with KA-like features (SCC-KA) (n = 8) for trisomy 7 by fluorescence in-situ hybridization (FISH) to determine if this chromosomal abnormality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…FISH studies have been demonstrated to be feasible in cutaneous tumours, revealing the presence of trisomy 7 in SCC 13 as well as 3p21 genetic deletion in poorly differentated SCCs and SCCs in situ. 14 In view of the numerous studies suggesting a relationship between MYC and SCC, the aim of our study was to investigate whether SCCs and ⁄or their precursor lesions (AKs) harboured MYC genomic aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH studies have been demonstrated to be feasible in cutaneous tumours, revealing the presence of trisomy 7 in SCC 13 as well as 3p21 genetic deletion in poorly differentated SCCs and SCCs in situ. 14 In view of the numerous studies suggesting a relationship between MYC and SCC, the aim of our study was to investigate whether SCCs and ⁄or their precursor lesions (AKs) harboured MYC genomic aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…FISH studies have been demonstrated to be feasible in cutaneous tumours, revealing the presence of trisomy 7 in SCC 13 as well as 3p21 genetic deletion in poorly differentated SCCs and SCCs in situ 14 …”
mentioning
confidence: 99%
“…Furthermore, Nangia et al (2001) demonstrated a correlation between trisomy 6 and metastatic potential in BCCs. Trisomy 7 has been observed in both SCC and KA, although not recurrently (Cheville et al, 1995). Dö bler et al (1999) investigated a number of common loci (3p21, 17p13, and 9p21) often observed to undergo deletion in SCC, BCC, KA, and SCC in situ.…”
Section: Interphase Fishmentioning
confidence: 98%
“…To solve these shortcomings, interphase fluorescence in situ hybridization (I-FISH), a useful technique for investigating chromosomal alterations in solid tumours, has been applied to interphase nuclei of tumour tissue from different anatomical sites. In both BCC and SCC tumours, previous FISH studies have reported the presence of chromosome alterations (Koyama et al, 2000;Cheville et al, 1995). However, in the literature there has not been any study regarding chromosomal alterations to the eyelid with BCC and SCC tumours.…”
Section: Introductionmentioning
confidence: 99%